Total Sialic Acid Concentrations as a Supporting Marker of Malignancy in Acute Lymphoblastic Leukemia - Sulaiman, Gh. M (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
To follow up the response of acute lymphoblastic leukemic (ALL) patients to chemotherapy treatment and for prognosis, diagnosis, the total Sialic acid (TSA) levels was studied as a tumor marker. The study included 40 patients (male = 22, female =18) with (ALL) were tested for the serum and leukocytes homogenate concentrations of total sialic acid (TSA) before and after treatment with six different chemotherapy protocols. While significantly increased ( P< 0.001 ) as compared to the heal thy individuals group, serum and leukocytes homogenate TSA concentrations dropped significantly ( P<O.OOl ) after treatment with each of the six chemotherapy treatment protocols, as compared to ALL untreated patients. A linear correlation relationship ( r2 = 0.951 4 ; r2 = 0.9451) was found between TSA concentrations and the period of chemotherapy treatment in serum and leukocytes homogenate. A linear correlation relationship (r2 = 0.9965) could be found between percentage of serum total sialic acid and percentage of leukocytes homogenate total sialic acid. The results of this study strongly support the role of TSA as a marker for the disease and suggest that it could be used for progression and prognosis of ALL patients, in addition we strongly suggest that there was a positive relationship between TSA level in serum and leukocytes.